A theoretical investigation of spectroscopy properties and transition properties of TlBr+ cation - Ming-jie Wan; Zheng-ce Jiang; Bary Ghulam; Xing-yong Huang; Duo-hui Huang (Scientific Reports)
Abstract The potential energy curves, dipole moments and transition dipole moments of the 14 Λ–S states and 30 Ω states of TlBr+ cation were performed using the multi-reference configuration interaction method. The Davidson correction and spin–orbit coupling effects were also considered. The spectroscopic properties and transition properties of TlBr+ cation were reported at the first time. The results show that the X 2Π is the ground state and the A 2Σ+ is the first excited state, which are both weakly bound states. 14 Λ–S states are all electronically bound except for the 24Π state, which is repulsive. The phenomenon of avoided crossing in the Ω states occurs in the energy region between 30,000 and 50,000 cm−1. The Franck–Condon factors, radiative lifetimes and emission coefficients between the $$A{}^{2}Σ_{1/2}^{ + } → X{}^{2}Π_{3/2}$$ and $$X{}^{2}Π_{{{1}/2}} → X{}^{2}Π_{3/2}$$ transitions are both calculated. The results indicated that the radiative lifetimes of the $$A{}^{2}Σ_{1/2}^{ + }$$ and $$X{}^{2}Π_{{{1}/2}}$$ states are too large to laser cooling TlBr+ cation, laser cooling of TlBr+ cation is not feasible. These results provide a theoretical basis to explore the spectroscopic properties of TlBr+ cation.